Enantioselective Synthesis and Pharmacological Evaluation of Aza-CGP37157-Lipoic Acid Hybrids for the Treatment of Alzheimer's Disease - Ángel Cores; Patrycja Michalska; José Miguel Pérez; Enrique Crisman; Clara Gómez; Mercedes Villacampa; José Carlos Menéndez; Rafael León (MDPI AG, 2022)
Hybrids based on an aza-analogue of CGP37157, a mitochondrial Na+/Ca2+ exchanger antagonist, and lipoic acid were obtained in order to combine in a single molecule the antioxidant and NRF2 induction properties of lipoic acid and the neuroprotective activity of CGP37157. The four possible enantiomers of the hybrid structure were synthesized by using as the key step a fully diastereoselective reduction induced by Ellman's chiral auxiliary. After computational druggability studies that predicted good ADME profiles and blood-brain permeation for all compounds, the DPPH assay showed moderate oxidant scavenger capacity. Following a cytotoxicity evaluation that proved the compounds to be non-neurotoxic at the concentrations tested, they were assayed for NRF2 induction capacity and for anti-inflammatory properties and measured by their ability to inhibit nitrite production in the lipopolysaccharide-stimulated BV2 microglial cell model. Moreover, the compounds were studied for their neuroprotective effect in a model of oxidative stress achieved by treatment of SH-SY5Y neuroblastoma cells with the rotenone-oligomycin combination and also in a model of hyperphosphorylation induced by treatment with okadaic acid. The stereocenter configuration showed a critical influence in NRF2 induction properties, and also in the neuroprotection against oxidative stress experiment, leading to the identification of the compound with S and R configuration as an interesting hit with a good neuroprotective profile against oxidative stress and hyperphosphorylation, together with a relevant anti-neuroinflammatory activity. This interesting multitarget profile will be further characterized in future work.